An Analytical Study of some of the Kinematic Variables of World Champions with Long Jump (Daegu) in South Korea (2011) - Mutasher, Dr. Shatha Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to know that any sporting achievement requires knowledge of many mechanical and influencing factors, and failure to achieve is due to neglect of some factors, and this is why achievement is one of the most difficult things facing sports training in its field. The effectiveness of the long jump is from activities that have its own technical and physical requirements starting from the speed of the projectile (here the player's body is the projectile) to the starting angle and body position and the correct mechanical connection of these variables. The jump competitions entered into the Olympic representation and that since the year (1896). The first modern Olympics in Greece, and the tracker of global sporting achievements sees that sport is in a permanent and continuous development, and the effectiveness of the long jump has received attention to The experiences, which helped us to find the most important factors that, must be taken care of focus on to raise. The level of achievement towards a better. Kinetic analysis used to determine the level of performance of movements and mathematical skills of players accurately and through which the values of the kinematic variables; can be extracted and compared with typical kinematic variables, knowing the strengths and weaknesses in the player’s performance and contributing to adjusting this performance for the better. The research problem were noted differences in the level of achievement for the players, the long jump as compared to men cause lack of linkage between these variables under study during the performance. Which was formed first, the omission of some trainers for training-related aspect of physical Secondly. The lack of adequate attention to the analysis motor for the players felt that the researcher studies a comparison of some variables kinematics to accomplish the global men and women's championship (Daegu) in South Korea (2011) to be a good model for the kinetic model for both sexes, and to know the strengths and weaknesses they have.